2013
DOI: 10.1128/aem.02653-13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diarrhea-Associated Virulence Genes and Genetic Diversity in Escherichia coli Isolates from Fecal Material of Various Animal Hosts

Abstract: In order to assess the health risk associated with a given source of fecal contamination using bacterial source tracking (BST), it is important to know the occurrence of potential pathogens as a function of host. Escherichia coli isolates (n ‫؍‬ 593) from the feces of diverse animals were screened for various virulence genes: stx 1 and stx 2 (Shiga toxin-producing E. Eleven hosts were positive for only the eae (10.11%) gene, representing atypical EPEC, while two hosts were positive for both eae and EAF (1.3%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
4
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 51 publications
5
53
4
4
Order By: Relevance
“…There are also no published case reports describing the clinical features of STEC infection in horses. The available published data on the prevalence of STEC in horses (85)(86)(87)(88) and donkeys (84,89,90) indicate that they are not major reservoirs of STEC and may instead be spillover hosts. Only one of 400 horse fecal samples screened in Germany was positive for STEC.…”
Section: Equinementioning
confidence: 99%
See 1 more Smart Citation
“…There are also no published case reports describing the clinical features of STEC infection in horses. The available published data on the prevalence of STEC in horses (85)(86)(87)(88) and donkeys (84,89,90) indicate that they are not major reservoirs of STEC and may instead be spillover hosts. Only one of 400 horse fecal samples screened in Germany was positive for STEC.…”
Section: Equinementioning
confidence: 99%
“…They include llamas, moose, alpacas, antelopes, and yaks (79)(80)(81)(82)(83)(84). These animals can transmit STEC to humans directly by contact at petting zoos or indirectly through fecal deposition in water sources, vegetable fields, or recreational areas or on meat.…”
Section: Bison (Bison Bison)mentioning
confidence: 99%
“…However, several diarrheagenic pathotypes, such as Shiga toxin-producing E. coli (STEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), enteroinvasive E. coli (EIEC), and enteroaggregative E. coli, have been recognized (1) and implicated in many waterborne outbreaks (2,3,4). Several studies have shown that fecal material from various animals and humans contains E. coli carrying virulence genes associated with pathogenic E. coli (5,6,7,8) and can be a potential source of pathogenic E. coli in the surface waters. In recent years, various phenotypic and genotypic (library-dependent or library-independent) bacterial source tracking (BST) methods (9) have been developed to identify the source of fecal pollution in order to protect and manage source water quality and also to assess the potential public health risk associated with fecal contamination from a particular host source.…”
mentioning
confidence: 99%
“…Despite the large amount of data available on the occurrence of pathogenic E. coli in different animals (5)(6)(7)(8), only limited information on the prevalence of pathogenic E. coli in a wide range of avian host sources is available. For instance, the occurrence of STEC and EPEC has been previously found in some wild birds in Europe, Japan, and the United States, but these studies were limited to only gull and pigeon (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…However, other animals, such as sheep, goats, swine, birds, wild animals, and humans, can also harbor STEC strains in their digestive tracts (35)(36)(37). For typical EPEC, the only reservoir is humans, whereas for atypical EPEC, both humans and other animals can be reservoirs (37).…”
mentioning
confidence: 99%